Responsiveness of human bronchial fibroblasts and epithelial cells from asthmatic and non-asthmatic donors to the transforming growth factor-β(1) in epithelial-mesenchymal trophic unit model - Paw, Milena (BMC Mol Cell Biol, 2021)
BACKGROUND: The asthma-related airway wall remodeling is associated i.a. with a damage of bronchial epithelium and subepithelial fibrosis. Functional interactions between human bronchial epithelial cells and human bronchial fibroblasts are known as the epithelial-mesenchymal trophic unit (EMTU) and are necessary for a proper functioning of lung tissue. However, a high concentration of the transforming growth factor-β(1) (TGF-β(1)) in the asthmatic bronchi drives the structural disintegrity of epithelium with the epithelial-to-mesenchymal transition (EMT) of the bronchial epithelial cells, and of subepithelial fibrosis with the fibroblast-to-myofibroblast transition (FMT) of the bronchial fibroblasts. Since previous reports indicate different intrinsic properties of the human bronchial epithelial cells and human bronchial fibroblasts which affect their EMT/FMT potential beetween cells derived from asthmatic and non-asthmatic patients, cultured separatelly in vitro, we were interested to see whether corresponding effects could be obtained in a co-culture of the bronchial epithelial cells and bronchial fibroblasts. In this study, we investigate the effects of the TGF-β(1) on the EMT markers of the bronchial epithelial cells cultured in the air-liquid-interface and effectiveness of FMT in the bronchial fibroblast populations in the EMTU models. RESULTS: Our results show that the asthmatic co-cultures are more sensitive to the TGF-β(1) than the non-asthmatic ones, which is associated with a higher potential of the asthmatic bronchial cells for a profibrotic response, analogously to be observed in '2D' cultures. They also indicate a noticeable impact of human bronchial epithelial cells on the TGF-β(1)-induced FMT, stronger in the asthmatic bronchial fibroblast populations in comparison to the non-asthmatic ones. Moreover, our results suggest the protective effects of fibroblasts on the structure of the TGF-β(1)–exposed mucociliary differentiated bronchial epithelial cells and their EMT potential. CONCLUSIONS: Our data are the first to demonstrate a protective effect of the human bronchial fibroblasts on the properties of the human bronchial epithelial cells, which suggests that intrinsic properties of not only epithelium but also subepithelial fibroblasts affect a proper condition and function of the EMTU in both normal and asthmatic individuals. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12860-021-00356-8.